Death receptor signaling - Lavrik, Inna N.; Golks, Alexander; Krammer, Peter H. (Journal of cell science, 2005)
Apoptosis or programmed cell death is a common property of multicellular organisms ([Danial and Korsmeyer, 2004][1]; [Krammer, 2000][2]). It can be triggered by a number of factors, including UV- or γ-irradiation, chemotherapeutic drugs or signaling by death receptors (DR). The DR family is part of
Gesehen am 02.03.2021